Evolutionary sex allocation theory explains sex ratios in natural Plasmodium falciparum infections. Issue 8 (July 2019) - Schneider, Petra; Babiker, Hamza A.; Gadalla, Amal A.H.; Reece, Sarah E.
Graphical abstract: Highlights: We apply evolutionary sex allocation theory to Plasmodium falciparum in natural infections. Gametocyte sex ratios and densities are negatively correlated (fertility insurance) Fertility insurance is more apparent in the dry compared with the transmission season. Sex ratios differ between single and mixed genotype infections, but not as expected. Mixed genotype infections do not have higher sex ratios (no local mate competition) Abstract: Malaria transmission is achieved by sexual stages, called gametocytes, and the proportion of gametocytes that are male versus female (sex ratio) influences transmission success. In malaria model systems, variation in gametocyte sex ratios can be explained by the predictions of evolutionary sex allocation theory. We test these predictions using natural Plasmodium falciparum infections. The predicted negative correlation between sex ratio and gametocyte density holds: the sex ratio increases when gametocyte densities decrease, and this is most apparent in single genotype infections and in the dry season. We do not observe higher gametocyte sex ratios in mixed compared with single genotype infections.